Social Capital and Household Welfare Among Anioma People in Delta State, Nigeria. - ONYEMENAM, CHRISTIAN ’EDOZI (Advances in Social Sciences Research Journal, 2019)
Most studies on social capital and household welfare have focused largely on econometric analyses of formal networks while informal, less institutionalised but durable networks are either ignored or concepts like ‘trust’, and ‘age groups’ are reduced to equations in econometric models that leaves out the quintessential social aspects. This non-econometric study focused on informal networks and social relations, using ethnographic and cross-sectional survey data from 13 homogenous Anioma communities in Delta State, Nigeria. Descriptive and inferential statistics were used to analyse the primary data while content analysis was used for the ethnographic data. Among others, the study found that access to social capital was not gender sensitive, it was not significantly related to welfare but it is positively correlated with household per capita income. Finally, while there was a large stock of social capital, household welfare remained low, due to the high level of poverty and the influence of the communal value that places an obligation on those who have more than others to help, such that they become ‘drawn back’, by their stock of social capital, which becomes an encumbrance of a kind. Accordingly, government should invest in informal social capital and incorporate it in its development policies and implementation plans, so as to help remove the ‘draw backs,’ foster healthy relations between community-level organisations and kinship-based networks and involve both types of social capital in its pro-poor programmes. Key words: social capital, household welfare, informal networks, social relations, ethnographic data.